Spectrophotometric analysis of color changes in teeth incinerated at increasing temperatures. (July 2015) - Rubio, Leticia; Sioli, Jose Manuel; Suarez, Juan; Gaitan, Maria Jesus; Martin-de-las-Heras, Stella
Highlights: Colorimetric variables estimated the temperature of exposure of incinerated teeth. Temperatures of 200° and 400° C were estimated by lightness with high accuracy. Temperatures between 800° and 1200 °C by lightness, chromaticity b and yellowness index. Whiteness index for temperatures of 1000° and 1200 °C. Lightness was the most useful color variable to estimate temperature of exposure. Abstract: Color changes produced by histological alterations in burned teeth can provide conclusive forensic information on the temperature of exposure. The objective was to correlate heat-induced color changes in incinerated teeth with increases in temperature (to 1200 °C). Spectrophotometry was used to measure lightness, chromaticity ( a* and b* ), whiteness, and yellowness in 80 teeth heated at temperatures of 100, 200, 400, 600, 800, 1000, or 1200 °C for 60 min. Chromaticity a* was reduced at 100 °C and lightness at 200 and 400 °C, while chromaticity b* and yellowness were reduced at 400 and 600 °C. Higher temperatures (800, 1000, and 1200 °C) produced progressive increases in lightness and whiteness but reductions in chromaticity b* and yellowness. The accuracy of color values to determine the temperature of exposure was determined by Receiver Operating Characteristic analysis. High accuracy was shown by lightness, chromaticity b* and yellowness values for temperatures between 800° and 1200 °C, by whiteness for temperatures of 1000° and 1200 °C, and by lightness for temperatures of 200° and 400 °C, with sensitivity and specificity values ranging from 90% to 100%. According to these results, colorimetric analysis of incinerated teeth can be used to estimate the temperature of exposure with high accuracy, with lightness being the most useful variable.